Cálculo neutrónico de reactores híbridos fusión-fisión. - Schmidt, Norberto S. (Comisión Nacional de Energía Atómica. Instituto Balseiro, 2019)
Fil. Schmidt, Norberto S.. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina